VALIDATION OF LC-MS/MS METHOD FOR THE SIMULTANEOUS ESTIMATION OF ITRACONAZOLE AND ITS METABOLITE HYDROXY ITRACONAZOLE IN PLASMA - haq, kashif ul; Kumar, Nitesh (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To develop and validate a sensitive, selective and reproducible method for the estimation of Itraconazole (ITR) and its pharmacologically active metabolite hydroxy Itraconazole (HITR) in human CPDA (Citrate Dextrose Phosphate Adenine) plasma, using Loratadine (L) as an internal standard (IS). Methods: The drugs of interest and IS were extracted by solid phase extraction technique, using HLB cartridges (30mg/1cc). Chromatographic separation was achieved in 2.6 minutes on reverse phase Hypersil Gold (50Ã—4.6) mm, 3Âµ column, using isocratic elution with methanol-buffer solution (2 Mm Ammonium acetate) in proportion ofÂ (90:10, v/v). Tandem mass spectrometer was used to detect the positive ions in the MRM (Multiple Reaction Monitoring) mode. Results: The method was linear for ITR (1.08-403.28 ng/ml) and HITR (1.09-406.77 ng/ml) and the coefficient of correlation (r) for the drug and the metabolite were better than 0.99 during the three precision and accuracy batch. The method was fully validated, complying FDA (Food and Drug Administration), EMEA (European Medicines Agency) guideline and recommendations of AAPS (American Association of Pharmaceutical Scientists) white papers demonstrating Selectivity, Sensitivity, Matrix factor, Precision and Accuracy, Linearity, Aqueous stability, Stability in biological matrix, Dilution Integrity, Reinjection Reproducibility, Recovery, Ruggedness and Extended Batch Verification. Conclusion: The validated method is applicable for Bioavailability/ Bioequivalence and Pharmacokinetic studies. Keywords: Itraconazole; Hydroxy Itraconazole; LC-MS/MS; Bioavailability, Bioequivalence.